Facilitating and inhibiting factors related to treatment adherence in women with polycystic ovary syndrome: A qualitative study - Fatemeh Bazarganipour; Seyed Abdolvahab Taghavi (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Adherence issues in polycystic ovary syndrome (PCOS) patients have not been examined thoroughly. Patients report prolonged periods of treatment and side effects of the drug as the most common reason for withdrawal from treatment. To improve the effective management of PCOS patients, it is fundamental to understand facilitating and inhibiting factors to treatment adherence. Objective: To explore facilitating/inhibiting factors related to treatment adherence among PCOS patients. Materials and Methods: This was a qualitative study with a purposive sample of women with confirmed diagnosis of PCOS. The data were collected via 20 in-depth semi-structured interviews with women aged between 21-34 yr. A qualitative content analysis was used to analyze the data. Results: Five themes were identified which described different types of facilitating/ inhibiting factors to treatment adherence. Inhibiting factors included financial issues, patient-related, disease-related, and health care provider-related factors; while social factors were found to be both facilitating and inhibiting. Conclusion: The findings suggest that successful adherence to PCOS treatment is highly dependent on patients recognizing and adapting to financial, social, and health care related inhibiting factors. It is also crucial for clinicians and policy makers to recognize these key inhibiting factors in order to improve treatment outcomes.